Foxconn and the serial suicide crisis - Yeung, Jeff Hoi Yan, (SAGE Knowledge. Cases., 2014)
Foxconn began its long journey to become a giant original equipment manufacturer in the 1970s and is now the largest multinational electronics contract manufacturer. However, in 2010 its serial employee suicides in China-based plants fell under the media spotlight and attracted worldwide attention. This crisis revealed serial operational problems. The reactions of media, the public, Foxconn's customers and employees, scholars, and the Chinese Government are examined. The case then shows how the serial suicides were caused by operations issues, including labor wage control, and a semi-military management style based on the Taylor paradigm, and how they affected the decision about plant migration. Students are expected to discuss the background of the case, analyze the situation and reactions, learn the operations management issues involved, and recommend corrective actions to address related problems.